TINGKAT KEBERHASILAN PENETASAN TELUR PENYU LEKANG (Lepidochelys olivacea) DI PANTAI PELANGI BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Saputri, Ira Dyah; Budiantoro, Agung (Universitas Jambi, 2025)
One type of sea turtle that often lands to lay eggs on the South coast of the Special Region of Yogyakarta is the Olive Ridley turtle (Lepidochelys olivacea). The last study on the hatching success rate of olive ridley turtles on Pelangi Beach in 2019 was only in semi-natural nests. Currently, on Pelangi Beach, hatching has begun using sand media placed in buckets to avoid rain. This study aims to analyze the comparison of the hatching success rate of olive ridley turtle eggs in semi-natural nests with buckets and environmental factors that support hatching success at Pelangi Beach, Bantul Regency, DIY. The method used is direct observation of the hatching rate from semi-natural methods and buckets with four nests each. Descriptive analysis was carried out to compare the hatching results in the semi-natural nest method with the bucket container nest. Environmental factors in both methods were observed during the incubation process till hach and then compared to determine the differences in environmental factors between methods. The results showed that the percentage of hatching success rate of Olive Ridley turtle eggs was higher in the bucket hatching method (79.00 ± 14.48%), compared to the semi-natural hatching method (74.11 ± 15.84%). Environmental factors between semi-natural and bucket methods in the form of pH, Temperature are not significantly different while the humidity in the bucket is higher than in the semi-natural nest. The results of the study can be concluded that the hatching method using a bucket container is better than using a semi-natural nest, this is because the humidity in the bucket container method is optimally maintained than in a semi-natural nest.